Grammaticalization : studies in Latin and Romance morphosyntax - Klausenburger, Jürgen (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2000)
In this monograph, various aspects of the morphosyntactic evolution of the Romance languages are shown to interact in a theory of grammaticalization. The study argues for the incorporation and subordination of inflectional morphology within a grammaticalization continuum, constituting but a portion of the latter. Parameters of natural morphology are seen as principles of grammaticalization, but the reverse is also true, rendering grammaticalization and natural morphology indistinguishable. In the context of this theoretical framework, Chapter 2 deals with Latin, French, and Italian verbal infl.